Of Religion and Empire : Missions, Conversion, and Tolerance in Tsarist Russia - Khodarkovsky, Michael, 1955-; Geraci, Robert P. (Book collections on Project MUSE., 2001)
Russia's ever-expanding imperial boundaries encompassed diverse peoples and religions. Yet Russian Orthodoxy remained inseparable from the identity of the Russian empire-state, which at different times launched conversion campaigns not only to "save the souls" of animists and bring deviant Orthodox groups into the mainstream, but also to convert the empire's numerous Muslims, Buddhists, Jews, Catholics, and Uniates. This book is the first to investigate the role of religious conversion in the long history of Russian state building. How successful were the Church and the state in proselytizing among religious minorities? How were the concepts of Orthodoxy and Russian nationality shaped by the religious diversity of the empire? What was the impact of Orthodox missionary efforts on the non-Russian peoples, and how did these peoples react to religious pressure? In chapters that explore these and other questions, this book provides geographical coverage from Poland and European Russia to the Caucasus, Central Asia, Siberia, and Alaska. The editors' introduction and conclusion place the twelve original essays in broad historical context and suggest patterns in Russian attitudes toward religion that range from attempts to forge a homogeneous identity to tolerance of complexity and diversity. Contributors: Eugene Clay, Arizona State University; Robert P. Geraci, University of Virginia; Sergei Kan, Dartmouth College; Agnes Kefeli, Arizona State University; Shoshana Keller, Colgate University; Michael Khodarkovsky, Loyola University, Chicago; John D. Klier, University College, London; Georg Michels, University of California, Riverside; Firouzeh Mostashari, Regis College; Dittmar Schorkowitz, Free University, Berlin; Theodore Weeks, Southern Illinois University; Paul W. Werth, University of Nevada, Las Vegas